2015
DOI: 10.1080/15226514.2014.935286
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Repeated Phytoextraction of Cadmium and Zinc from an Agricultural Soil Contaminated with Sewage Sludge

Abstract: Long-term application of sewage sludge resulted in soil cadmium (Cd) and zinc (Zn) contamination in a pot experiment conducted to phytoextract Cd/Zn repeatedly using Sedum plumbizincicola and Apium graceolens in monoculture or intercropping mode eight times. Shoot yields and soil physicochemical properties changed markedly with increasing number of remediation crops when the two plant species were intercropped compared with the unplanted control soil and the two monoculture treatments. Changes in soil microbia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Heavy metal pollution from industrial and agricultural activities has become a worldwide concern (Akesson et al, 2014). Given that heavy metals are persistent and non-degradable, their contamination of soil is irreversible and leads to a decline in soil fertility as well as in crop yield and quality (Luo et al, 2015). Heavy metals accumulated in plants and animals can enter the food chain and subsequently harm human health (Iqbal et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Heavy metal pollution from industrial and agricultural activities has become a worldwide concern (Akesson et al, 2014). Given that heavy metals are persistent and non-degradable, their contamination of soil is irreversible and leads to a decline in soil fertility as well as in crop yield and quality (Luo et al, 2015). Heavy metals accumulated in plants and animals can enter the food chain and subsequently harm human health (Iqbal et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…To achieve this goal, co-cropping (e.g., inter-cropping and mixed cropping) techniques using hyperaccumulators along with some crops are often applied. For example, Luo et al [7] showed that co-cropping the hyperaccumulator Sedum plumbizincicola and the main crop, celery (Apium graveolens), increased Cd uptake by S. plumbizincicola while reducing Cd accumulation by celery. Some metal-accumulating crop plants have the advantages of large biomass, welldeveloped main roots, and strong adaptability [8].…”
Section: Introductionmentioning
confidence: 99%
“…Alfalfa seeds were purchased from Jiangsu Provincial Academy of Agricultural Sciences (JAAS), and seeds of Sedum plumbizincicola, a Cd and Zn hyperaccumulator, 27,28,30,31,34 were collected from a Pb−Zn mine area in the suburbs of Hangzhou city, Zhejiang province, east China. Seeds of alfalfa were cultured using nonpolluted soil in a greenhouse for preincubation before seedlings of similar height with healthy well-developed root systems were selected for transplanting.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%